Evaluación de prendimiento de injerto del cacao trinitario (Theobroma cacao l.) utilizando la influencia lunar en el cantón Pujili año 2012- 2013 - Unaucho Ninasunta, Marcelo (2014)
The present research was carried out at Mr. Unaucho Carlos’ farm that is located in Puembo recinto, La Esperanza parish, Pujilí canton, Cotopaxi province. The research lasted for 120 days of fieldwork. It was a kind of experimental research and a correlational study was used in order to encourage the variables to assess the Trinitarian cacao graft with the influence of lunar phases. The experimental design used is the completely random design (DCA) with four treatments, seven replications, and 10 experimental units. It was permitted to see that the highest percentage of grafting was the new moon with 95,71….